Noninvasive and quantitative evaluation of movement disorder disability using an infrared depth sensor - Tsukagoshi, Setsuki; Furuta, Minori; Hirayanagi, Kimitoshi; Furuta, Natsumi; Nakazato, Shogo; Fujii, Motoaki; Yuminaka, Yasushi; Ikeda, Yoshio (Journal of clinical neuroscience, 2020)
•Neurodegenerative disorders feature difficult-to-assess movement disabilities.•Usefulness of an infrared depth sensor device for quantitative assessment was investigated.•Gait analyses of ataxic, Parkinson’s disease, and control subjects were conducted.•Sensor assessments agreed with clinical scale scores, indicating future clinical utility. Cerebellar ataxia and Parkinson’s disease are neurodegenerative disorders clinically characterized by motor disabilities including gait disturbance. This study aimed to investigate the usefulness of an infrared depth sensor device to quantitatively evaluate gait disturbances in patients with movement disorders. 25 ataxic, 25 Parkinson’s disease, and 25 control subjects were enrolled and evaluated their walk. Stride length, feet interval, gait rhythm, and a ratio of the actual walking route length to the linear distance between the start and goal points (A/L ratio) were assessed and compared. Outcome correlations with clinical scales were also analyzed. The average stride length was shorter in ataxic subjects or Parkinson’s disease subjects than in control subjects. The average feet interval was larger in ataxic subjects than in control subjects. The stride length coefficient of variation (CV), gait rhythm CV, and average and standard deviations of the A/L ratio were larger in ataxic or Parkinson’s disease subjects than in control subjects. Ataxic subjects exhibited significant positive correlations between the CV of stride length or average feet interval and scale for the assessment and rating of ataxia scores or international cooperative ataxia rating scale scores. Parkinson’s disease subjects exhibited a significant correlation between the average stride length, CV of stride length, or standard deviation of A/L ratio and unified Parkinson's disease rating scale score. The device used in this study differentiated the characteristics of gait disturbance in each movement disorder and quantitatively evaluated ataxia or Parkinson’s disease severity, indicating its potential clinical utility across applications.